2016
DOI: 10.1142/s1363919616500043
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Green Innovation in the Search of Competitive Advantage of Enterprises of the Electrical and Electronic Brazilian Sectors

Abstract: This study aimed to verify how the adoption of green innovations influences in the obtention of competitive advantage of companies in the electrical and electronic Brazilian sectors. Quantitative in nature, the study adopted the conceptual model proposed by [Chen et al. (2006). The influence of green innovation performance on corporate advantage in Taiwan. Journal of Business Ethics, 67(4), 331-339]. Using as target population companies linked to the Brazilian Association of Electrical and Electronics Industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…also stated that product innovation is considered a main factor in building competitive advantage, which should support long-term business performance. Additionally, the results are consistent with other studies such asMa et al (2017) andArenhardt et al (2016), in concluding that firms which are dynamically involved in green innovation may improve stakeholders' opinions and improve the image of the firm, making them stand out among the competition, thus increasing their competitiveness, influence and appeal to achieve long-term success. Qui et al (2019) also indicated that green product innovation is positively correlated with competitive advantage in the Chinese manufacturing industry, indicating that this is also pertinent to manufacturing in developing countries (having been well known for some time in developed economies).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…also stated that product innovation is considered a main factor in building competitive advantage, which should support long-term business performance. Additionally, the results are consistent with other studies such asMa et al (2017) andArenhardt et al (2016), in concluding that firms which are dynamically involved in green innovation may improve stakeholders' opinions and improve the image of the firm, making them stand out among the competition, thus increasing their competitiveness, influence and appeal to achieve long-term success. Qui et al (2019) also indicated that green product innovation is positively correlated with competitive advantage in the Chinese manufacturing industry, indicating that this is also pertinent to manufacturing in developing countries (having been well known for some time in developed economies).…”
supporting
confidence: 89%
“…Aside from its defining characteristic as a key determinant of superior performance and a strong market position (Aboumoghli and Al-Abdallah, 2018), competitive advantage is of significant importance in numerous financial and nonfinancial indicators, such as the value of firms' intangible assets, such as brand identity (Chen, 2007). In this sense, competitive advantage can be gained through environmentally friendly products, green design and clean production processes (Arenhardt et al , 2016; Chuang and Huang, 2015). Aside from the positive brand identity associated with green activities (when communicated effectively to stakeholders), green product innovation meets legislative and regulatory environmental regulations and serves to build barriers and tone market entrants (Chen et al , 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have found a positive and significant relationship between GI and enterprise performance (Tang et al, 2018; Zhang et al, 2019). Specifically, GI has a positive effect on benefit, competitive advantage, and ecological reputation of enterprises (Arenhardt et al, 2016; Dangelico, 2017; Yang et al, 2016). Woo et al (2014) indicated that GI can increase labor productivity of manufacturing industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is no consensus on the impact on enterprise of GI. Although many studies have confirmed that GI has a positive impact on enterprises (Arenhardt et al, 2016; Tang et al, 2018; Xie et al, 2015), some studies indicated that expenditure on environmental activities may reduce the productivity of enterprises, and scholars worry that green investment cannot recover its cost (Palmer et al, 1995; Walley & Whitehead, 1994). Starting from these considerations, the objective of this paper is to investigate empirically how GI affects enterprise value and its mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that SCP emphasizes sustainable urban development; as major emitters of pollution, heavy polluters are under more policy pressure. This forces themselves to upgrade or innovate, which can boost its total factor productivity (Arenhardt et al 2016 ). Third, we find that SCP has a greater impact on non-CE than on CE.…”
Section: Resultsmentioning
confidence: 99%